Icariside II induces ferroptosis through the down-regulation of SLC7A11 in ovarian cancer - Donglan Yuan; Ting Guo; Xiaotong Zhu; Weiwei Song; Dengyun Nie; Hong Yu (Journal of Ovarian Research)
Abstract Background Ovarian cancer (OV) is the leading cause of death among gynecological malignancies. This study aimed to investigate the influence of Icariside II on OV in vitro and in vivo and to elucidate whether Icariside II induces ferroptosis in OV cells by regulating SLC7A11 expression. Methods SKOV3 cells and OV nude mice were treated with Icariside II, a control-plasmid or an SLC7A11-plasmid. EdU assay, flow cytometry, wound-healing assay, and Transwell assays were used to assess cell proliferation, apoptosis, migration, and invasion respectively. Total iron, Fe2+ levels, and intracellular lipid reactive oxygen species (ROS) stimulation were evaluated in both cells and tissues. Levels of cysteine (Cys), glutathione (GSH), and glutathione peroxidase 4 (GPX4) were also analyzed. Ferroptosis markers, including Ptgs2, Chac1, SLC7A11, and apoptosis-associated genes (Bax and Bcl-2), were detected using qRT-PCR, western blotting, and immunohistochemistry (IHC). SLC7A11 expression in OV was explored using data from The Cancer Genome Atlas (TCGA), and validated with IHC staining. Results Icariside II-induced ferroptosis in OV cells was confirmed by elevated Fe2+ and total iron levels, enhanced lipid ROS levels, higher Ptgs2 and Chac1 mRNA levels, and reduced levels of SLC7A11, Cys, GSH, and GPX4 in both in vitro and in vivo models. These effects were partially reversed by the SLC7A11-plasmid. Moreover, Icariside II suppressed SKOV3 cell proliferation, inhibited cells migration and invasion, and promoted apoptosis by downregulating SLC7A11 expression. Furthermore, we found that SLC7A11 expression was upregulated in OV tissues compared to adjacent non-tumor tissues. Conclusion Icariside II induces ferroptosis in OV by downregulating SLC7A11 expression in vitro and in vivo. Our study identified Icariside II as a promising therapeutic agent for the treatment of OV.